ANALISIS KOMPONEN REVERSE MEAN PADA HARGA SAHAM MELALUI PERSPEKTIF EKONOMI MAKRO DI BURSA EFEK JAKARTA - Aster Indah Widowati; Atim - Djazuli; M. Syafi’ie - Idrus (Sekolah Pascasarjana Universitas Brawijaya, 2010)
ABSTRACTSReverse mean reversion and predictability of stock return is probably the most well researched topic in the empirical research of financial economics. Numerous empirical studies have been unable to reject the hypothesis that return unpredictable and that stock price follows a random walk or martingale process. The essence of the mean-reversion hypothesis is that the stocks price contains a temporary component. Thus, the market value of stock deviates from the fundamental value but will revert to its mean. The objective of this study is to test the mean reversion hypothesis in Indonesian capital market, by investigate the size and significance of mean reversion component of stock prices at the Jakarta Stock Exchange, for the period of January 1990 through December 2003, and to investigate the size of the forecast error variance decomposition for real stock prices which is caused by permanent innovation and temporary innovation for a horizon of 2, 3, 4, 6, 12 and 24 months. By placing appropriate structural restrictions on a vector auto-regressive system estimated for the period of January 1990 through December 2003, it was found that the temporary component in the stock prices at the Jakarta Stock Exchange has significant size. From this, it can be inferred that the pattern of share price movements at the Jakarta Stock Exchange has a temporary component which will gradually disperse or undergo reverse mean. This evidence supports the mean reversion hypothesis that stock price are not pure random walks and predictability of stock return and reject the random walk hypothesis. Keywords: Reverse mean component, Macroeconomic Perspective